2003
DOI: 10.1021/jm021030a
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Biological Activity of Nitro Heterocycles Analogous to Megazol, a Trypanocidal Lead

Abstract: As part of our efforts to develop new compounds aimed at the therapy of parasitic infections, we synthesized and assayed analogues of a lead compound megazol, 5-(1-methyl-5-nitro-1H-2-imidazolyl)-1,3,4-thiadiazol-2-amine, CAS no. 19622-55-0), in vitro. We first developed a new route for the synthesis of megazol. Subsequently several structural changes were introduced, including substitutions on the two rings of the basic nucleus, replacement of the thiadiazole by an oxadiazole, replacement of the nitroimidazol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
74
1
3

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(79 citation statements)
references
References 30 publications
1
74
1
3
Order By: Relevance
“…It was reported that the peak was quite specific spectral data [59][60][61][62]. The 13 C-NMR signal of CH=N function of azomethylene and C=C function of compounds 3a-h appeared at 133-147 ppm and 133-135 ppm, respectively.…”
Section: Resultsmentioning
confidence: 89%
“…It was reported that the peak was quite specific spectral data [59][60][61][62]. The 13 C-NMR signal of CH=N function of azomethylene and C=C function of compounds 3a-h appeared at 133-147 ppm and 133-135 ppm, respectively.…”
Section: Resultsmentioning
confidence: 89%
“…All spectra were recorded with appropriate background corrections. CD spectra were measured in the 200-260 nm range, at 310 K. Firstly, the spectrum of a free HSA solution (1.00 × 10 -6 M in PBS solution, pH = 7.4) was recorded and then the spectra resulting from the addition of the maximum (6) where θ is the observed CD (in milli-degrees), n is the number of amino acid residues (585 for HSA), 15 l is the path length of the cell (in cm) and C p is the molar concentration of HSA (1.00 × 10 -6 M). The α-helical content of free HSA, as well as bound with BZL, MTZ, NFX and MZ, can be calculated from the molar residual ellipticity (MRE) values at 208 (equation 7) and 222 nm (equation 8):…”
Section: Methodology For Spectroscopy Measurementsmentioning
confidence: 99%
“…5 Subsequently, several structural changes were introduced in MZ, including substitution on the two rings of the basic nucleus, replacement of the thiadiazole by an oxadiazole, replacement of the nitroimidazole part by a nitrofuran or a nitrothiophene, and substitutions on the exocyclic nitrogen atom; however, megazol is still more biologically active than its derivatives. 6,7 Human serum albumin (HSA) is one of the main water soluble proteins in the bloodstream. Among its functions stands out the biodistribution of different classes of drugs and xenobiotics, as well as small, hydrophobic, endogenous and exogenous molecules.…”
Section: Introductionmentioning
confidence: 99%
“…74 Em outro caso, o megazol, agente tripanocida, teve seu desenvolvimento descontinuado devido à toxicidade e mutagenicidade demonstrada em ensaios realizados in vivo. [75][76][77] Ademais, a presença do grupo nitro ligado a anéis aromáticos pode ser relacionada à incidência de efeitos tóxicos causados pela redução in vivo dos compostos nitroaromáticos. 14 A possibilidade de a atividade biológica ser dependente da ligação dos intermediários de nitrorredução ao DNA promove questionamentos sobre o caráter mutagênico e neoplásico dos nitrocompostos.…”
Section: Atividade Antineoplásicaunclassified